2019
DOI: 10.1016/j.anbehav.2019.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Testing the role of same-sex sexual behaviour in the evolution of alternative male reproductive phenotypes

Abstract: Male same-sex sexual behaviour (SSB), where males court or attempt to mate with other males, is common among animal taxa. Recent studies have examined its fitness costs and benefits in attempts to understand its evolutionary maintenance, but the evolutionary consequences of SSB are less commonly considered. One potential impact of SSB might be to facilitate the evolution of traits associated with less sexually dimorphic males, such as alternative reproductive tactics, by diverting costly aggression from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…In both Kauai and Oahu, flatwing segregates as a singlelocus X-linked trait [10,24]. Silent males are strongly disadvantaged in the context of sexual selection [26,27], but the phenotype nevertheless spread rapidly under selection from the fly. Flatwing males are capable of expressing the precise patterns of rhythmic forewing movement that produce song in normal-wing males [11].…”
Section: Introductionmentioning
confidence: 99%
“…In both Kauai and Oahu, flatwing segregates as a singlelocus X-linked trait [10,24]. Silent males are strongly disadvantaged in the context of sexual selection [26,27], but the phenotype nevertheless spread rapidly under selection from the fly. Flatwing males are capable of expressing the precise patterns of rhythmic forewing movement that produce song in normal-wing males [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, only five of the experimental studies explicitly tested hypotheses for male-male courtship display. Four of the studies tested the intrasexual competition hypothesis ( Boutin et al, 2016 ; Lane et al, 2016 ; Kuriwada, 2017 ; Rayner & Bailey, 2019 ), and two found evidence to support it ( Lane et al, 2016 ; Kuriwada, 2017 ). Further, a single study tested another hypothesis but ended up suggesting competition ( Abbassi & Burley, 2012 ).…”
Section: Survey Resultsmentioning
confidence: 99%
“…Different mechanisms of intrasexual competition were suggested in the experimental studies ( Table 2 ): male-male courtship display can be relevant for “resource defence” ( Elie, Mathevon & Vignal, 2011 ; Abbassi & Burley, 2012 ); it plays a role on “condition assessment” of the displayer or its opponents ( Abbassi & Burley, 2012 ); and males assess the displayer condition to modulate aggressiveness ( Lane et al, 2016 ; Kuriwada, 2017 ) by “diverting costly aggression” ( Rayner & Bailey, 2019 ), or to establish “dominance hierarchies” ( Oliveira & Almada, 1998 ; Ungerfeld, Ramos & Bielli, 2007 ; Wang et al, 2011 ; Ungerfeld et al, 2014 ); with dominant males performing more male-male courtship than subordinate ones ( Adachi & Soma, 2019 referring to Langmore & Bennett, 1999 ).…”
Section: Survey Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such sexual mimicry might coevolve with SSB because SSB can also reduce aggressive interactions during competition (44,45; but see ref. 46). However, same-sex tandems in termites are not likely to be directly comparable to alternative mating strategies such as those based on deception, because heterosexual pairing is the highest fitness option for all termites and represents a cooperative relationship.…”
Section: Discussionmentioning
confidence: 99%